How does the supernatant of Lactobacillus acidophilus affect the proliferation and differentiation activities of rat bone marrow-derived stromal cells? - Samadikuchaksaraei, A; Gholipourmalekabadi, M; Saberian, M; Abdollahpour Alitappeh, M; Shahidi Delshad, E (Cellular and Molecular Biology, 2016)
Low proliferation rate and unwanted differentiation of bone marrow-derived stromal cells (rBMSCs) during the frequent passages have limited the use of such cells in clinical cell therapy. Recently, the researchers have focused on the effects of the components produced by some bacteria on proliferation of the stem cells. In this study, we discussed the possible effects of the Lactobacillus acidophilus supernatant on proliferation and differentiation of the rBMSCs. For this aim, the cells were isolated from rat bone marrow, characterized by culturing on tissue specific differentiation media and stained. The cells (passage two) were treated with different concentrations of the L. acidophilus supernatant (0, 0.1, 0.3, 0.9, 3, 9 and 30 &mgr;l/ml) for 14 days. The proliferation and differentiation capacity of the cells were then determined by 3-(4,5-Dimethylthiazol-2-yl)-2,5-Diphenyltetrazolium Bromide (MTT assay) and tissue specific staining. The results showed a positive effect of the supernatant on the cell proliferation in 3 and 9 &mgr;l/ml concentrations, while did not affect the differentiation capacity of the rBMSCs. The current study strongly suggests the L. acidophilus supernatant as an alternative material that could be added to the media with aim of improvement in the proliferation rate of the rBMSCs without affecting their differentiation capacity.